One hour of internal precooling with cold water/menthol enhances cycling performance in a heat/wet stress environment: A pilot study - Rinaldi, Kévin; Collado, Aurélie; Trong, Than; Hue, Olivier (Biology of Sport, 2023)
The aim of this study was to compare precooling durations before aerobic performance in a heat/wet stress environment. Seven heat-acclimated and trained male cyclists completed 1-hour time trials in a hot and humid environment. Before each trial, the cyclists drank (1) a neutral beverage at 23°C during the 1-hour pre-exercise resting period (Neutral), (2) an ice-slush/menthol beverage at -1°C during the last 30 min of the resting period (Pre-30), or (3) an ice-slush/menthol beverage at -1°C during the 1-hour pre-exercise resting period (Pre-60). In each condition, the cyclists drank cold water/menthol at 3°C during the exercise. Performance was significantly higher in Pre-60 than in Pre-30 and Neutral conditions (condition effect: F(2,12)=9.50, p=0.003, ηp2=0.61), with no difference between Pre-30 and Neutral. During the resting period, rectal temperature was significantly lower in Pre-60 than in Pre-30 and Neutral (condition effect: F(2,12)=4.48, p=0.035, ηp2=0.43). Thermal comfort and rating of perceived exertion were not affected by conditions, but thermal sensation was positively affected in Pre-60 during the resting period (Friedman condition effect at 40, 45 and 60 minutes: χ2=6.74; df=2; p=0.035; χ2 =8.00; df=2; p=0.018; χ2 =4.90; df=2; p=0.086, respectively) and exercise (Friedman condition effect at 5 and 60 minutes: χ2 =6.62; df=2; p=0.037; χ2 =6.50; df=2; p=0.039, respectively). This study shows that 1 hour of precooling with an ice-slush and menthol beverage (1) improved performance in a 1-hour time trial, (2) had a cumulative effect with a cold water/menthol beverage during this exercise, and (3) decreased rectal temperature during the resting period. This precooling method enhances cycling performance in a heat/wet stress environment.